Bayt Al Qur'an Al Akbar Home of the World Qur'an Learning Center;Palembang, a Religious City, Builds Religious Moderation People - Sumarto Sumarto; Emmi Kholilah Harahap (Yayasan Literasi Kita Indonesia, 2021)
Palembang City is one of the big cities in Sumatra, there are also Medan City, Banda Aceh City and Lampung City which are growing rapidly in terms of education, social economy and culture. In this paper, the author wants to convey to readers that in the area of Sumatra Island, there is one area that is the center of learning the Qur'an, namely the city of Palembang. Palembang City is not only famous as a City of History where at that time there was a war with Dutch Colonialism, the AMPERA event or the Mandate for the Suffering of the People and other historical events. The author wants to look at the aspects of learning the Qur'an in Palembang City, one of which is the center of learning is Bayt Al Qur'an Al Akbar which is located in the Musi II Gandus area of Palembang City.